External and internal mechanical work in skate roller skiing - Hladnik, J.; Supej, M.; Jerman, B. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The total mechanical work (W_tot) performed by an athlete has been assessed in several sports but not in roller skating and cross-country skiing. W_tot consists of external (W*_ext) and internal mechanical work (W_int). W*_ext is the work required to move the subject`s center of mass (COM; W_ext) relative to the surroundings, including the work done on the environment (W_env), while W_int is the work required to move the subject`s segments relative to the COM (Saibene et al., 2003). The work done by the subject`s segments (W_seg) is part of W_tot and consists of W_int and W_ext.